2013
DOI: 10.1590/s1517-86922013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Queixas musculoesqueléticas e procedimentos fisioterapêuticos na delegação brasileira paralímpica durante o mundial paralímpico de atletismo em 2011

Abstract: Introduction: Athletics is an umbrella sport with high incidence of musculoskeletal injuries; however, the literature presents little information on injuries in Paralympics athletics. Objective: This study was to describe the profile of the musculoskeletal complaints, their anatomical locations, and physiotherapeutic resources used during the Paralympic Athletics World Championships in Christchurch in 2011. Methods: The Brazilian delegation included 34 athletes. Their musculoskeletal complaints, affected anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(22 reference statements)
0
2
0
2
Order By: Relevance
“…Foram localizados 11 estudos que enfocaram as lesões esportivas no atletismo. Oito apresentaram delineamento transversal [33][34][35][36][37][38][39][40] , 2 longitudinal 41,42 e 1 estudo de avaliação de intervenção cirúrgica 43 . Dos estudos transversais, 3 investigaram a ocorrência de lesões musculoesqueléticas em atletas Paralímpicos 33,35,36 e 1 observou a acuidade visual de atletas com deficiência visual durante o esforço físico 34 .…”
Section: Provas Lesõesunclassified
See 1 more Smart Citation
“…Foram localizados 11 estudos que enfocaram as lesões esportivas no atletismo. Oito apresentaram delineamento transversal [33][34][35][36][37][38][39][40] , 2 longitudinal 41,42 e 1 estudo de avaliação de intervenção cirúrgica 43 . Dos estudos transversais, 3 investigaram a ocorrência de lesões musculoesqueléticas em atletas Paralímpicos 33,35,36 e 1 observou a acuidade visual de atletas com deficiência visual durante o esforço físico 34 .…”
Section: Provas Lesõesunclassified
“…Oito apresentaram delineamento transversal [33][34][35][36][37][38][39][40] , 2 longitudinal 41,42 e 1 estudo de avaliação de intervenção cirúrgica 43 . Dos estudos transversais, 3 investigaram a ocorrência de lesões musculoesqueléticas em atletas Paralímpicos 33,35,36 e 1 observou a acuidade visual de atletas com deficiência visual durante o esforço físico 34 . Dois estudos analisaram a ocorrência de lesões em atletas de alto nível do atletismo brasileiro 38,39 , 1 investigou a ocorrência de fibromialgia em mulheres do atletismo 37 , e 1 realizou inquérito sobre lesões em corredores de rua em 2009 em corridas de São Paulo 40 .…”
Section: Provas Lesõesunclassified
“…26 This achievement is indicative of the development undergone by Brazilian athletes as well as of their improved performance at the competitive level and thus demonstrates the relevance of the efforts of the Brazilian Paralympic Committee to improve the training conditions and the athletes' medical, physical therapy, and physiologic assessments. 25 In summary, the strength of the right and left knee flexor and extensor muscles exhibited a gradual increase among the assessments. In parallel, a relationship between muscle imbalance and knee and thigh complaints was found at all three assessments after 1 yr.…”
Section: Discussionmentioning
confidence: 88%
“…24 This study did not identify any specific period of greater vulnerability to injury as a function of muscle imbalance. Corroborating the observations made by Silva et al 25 on the relevance of recording the musculoskeletal complaints reported by athletes, such complaints must be observed and recorded by a multiprofessional staff. In fact, the continuous care provided by a multiprofessional staff had a significant influence on the results achieved by the Brazilian team at the 2011 IPC World Athletic Championships held in Christchurch (New Zealand), which ranked third in the number of medals after China and England.…”
Section: Discussionmentioning
confidence: 99%